Systematic Literature Review: Islamic Integrated Maths from Hadith - Alghar, Muhammad Zia; Radjak, Dwi Setiawati; Santoso, Ahmad (MAXIMA : Jurnal Pendidikan Matematika, 2024)
Education in Indonesia aims to create students who are ethical, moral, and devoted to God Almighty. Islamic integrated mathematics learning is one of the bridges to achieve this goal. This research aims to discover and explore Islamic integrated mathematics derived from hadith. The systematic literature review method was used in this research. The data used were 20 scientific papers in the 2019-2023 range from the Google Scholar database obtained through the Publish and Perish application. Data was analyzed by identifying, reviewing, comparing, and interpreting all data. The results showed various hadith themes and mathematical concepts used in Islamic integrated mathematics. The results of this study can be helpful for teachers and lecturers as a learning resource to be applied in learning Islamic integrated mathematics.